2018
DOI: 10.1089/jop.2018.0036
|View full text |Cite
|
Sign up to set email alerts
|

Supraciliary Microstent in Refractory Open-Angle Glaucoma: Two-Year Outcomes from the DUETTE Trial

Abstract: Placement of a supraciliary microstent provides up to 24 months of effective IOP lowering for medication-refractory POAG patients while, on average, decreasing the requirement for ocular hypotensive medications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“… 28 Recent evidence has indicated that uveoscleral outflow may account for ∼50% of aqueous drainage in normal human eyes and is thought to be higher in glaucomatous patients, in whom redirection toward the uveoscleral pathway occurs. 29 31 There is also evidence that supraciliary microstenting has significant IOP-lowering capabilities 11 , 13 , 32 , 33 and does not face the IOP-lowering limitation of episcleral venous pressure that is encountered when targeting the conventional outflow pathways such as during trabecular bypass. However, it is also known that supraciliary devices may cause a scarring reaction that may limit success rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 28 Recent evidence has indicated that uveoscleral outflow may account for ∼50% of aqueous drainage in normal human eyes and is thought to be higher in glaucomatous patients, in whom redirection toward the uveoscleral pathway occurs. 29 31 There is also evidence that supraciliary microstenting has significant IOP-lowering capabilities 11 , 13 , 32 , 33 and does not face the IOP-lowering limitation of episcleral venous pressure that is encountered when targeting the conventional outflow pathways such as during trabecular bypass. However, it is also known that supraciliary devices may cause a scarring reaction that may limit success rates.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also known that supraciliary devices may cause a scarring reaction that may limit success rates. 8 , 29 , 32 The use of suitable materials that minimize and prevent tissue scarring and foreign body reactions has been suggested by Gigon and Shaarawy. 29 In preclinical studies in rabbits, the MINIject implant produced limited fibrous encapsulation around the device, and caused minimal inflammatory reaction in an animal model that is known for aggressive ocular fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…The Trabectome procedure lowered IOP by 33% at 6 months in its pivotal study [15]. In a non-randomized case series, the CyPass supraciliary microstent device lowered mean IOP by 29.4% at 6 months, 34.7% at 12 months, and by 31.4% at 24 months, with medication use reduced by 28.6% at 2 years; adverse events included cataract progression (12%), IOP spikes (11%), and hyphema (6%) [16, 17]. The CyPass device has recently been voluntarily recalled from the global marketplace because of safety concerns related to 5-year corneal endothelial cell loss [18].…”
Section: Discussionmentioning
confidence: 99%
“…Stand-alone CyPass (Alcon) implantation (n=65) was shown at 2 years in the DUETTE study to decrease IOP from a mean of 24.5±2.8 mmHg to 16.8±3.9 mmHg (−31% reduction) (n=32) with 56.3% having a 20% reduction of IOP from baseline and a mean medication reduction from 2.2±1.1 at baseline to 1.5±1.2 at 2 years. 16 At 2 years, 12 eyes (18.5%) required additional glaucoma surgery. 17 Success was defined as IOP between 6 and 21 mmHg on no medications (complete success: 29.2%) or on same or fewer medications (qualified success: 62.5%).…”
Section: Discussionmentioning
confidence: 99%